WAYS OF STUDYING THE TEXT OF CHINGIZ AITMATOV’S STORY “JAMILA” (International journal of artificial intelligence, 2026)
The name of the great Kyrgyz writer Chingiz Aitmatov stands alongside the great representatives of world literature who gained international recognition in the twentieth century. The artistic embodiment of major spiritual problems troubling humanity, reflected through the centuries-old past and present life of the Kyrgyz people and neighboring nations, their dreams and aspirations, joys and anxieties, and diverse human destinies, is the unifying feature of the writer’s works. This article discusses the ways of studying the writer’s story Jamila in literary education.